2014
DOI: 10.1177/0021955x14531972
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study and modeling of nanofoams formation from single phase acrylic copolymers

Abstract: Medium to low density thermoplastic nanofoams have previously been produced using nanoparticles as nucleating center. Here we show that by designing the molecular structure of the polymer matrix to achieve high CO 2 solubility while controlling the glass transition temperature, it is possible to produce nanofoams with cell nucleation densities as high as 10 16 /cm 3 without introducing nucleation aids. This was achieved by maximizing foam expansion without uncontrolled cell ripening for a series of acrylic cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 31 publications
5
51
0
Order By: Relevance
“…The MMA‐ co ‐EMA copolymers ( T g = 96°C) were found to be more effective than PEMA ( T g = 65°C), which under similar conditions produced foams with 345 nm cells and 79% porosity . The studies concluded that homogeneous nucleation theory was consistent with the experimental trends observed, which was captured in a foaming model …”
Section: Polymer Systems For Nanofoamssupporting
confidence: 53%
See 2 more Smart Citations
“…The MMA‐ co ‐EMA copolymers ( T g = 96°C) were found to be more effective than PEMA ( T g = 65°C), which under similar conditions produced foams with 345 nm cells and 79% porosity . The studies concluded that homogeneous nucleation theory was consistent with the experimental trends observed, which was captured in a foaming model …”
Section: Polymer Systems For Nanofoamssupporting
confidence: 53%
“…Under the sorption conditions (30 MPa and 35°C), all polymers were in the amorphous state and readily foamed upon depressurization (1S process). Copolymers with T g between 85°C and 105°C produced nanofoams with cell size between 100 and 200 nm with porosities between 60 and 80% . Some higher T g polymers with high CO 2 solubility, such as MMA‐ co ‐PFMA, gave foams with 70 nm cell and 60% porosity and remarkably high cell nucleation densities.…”
Section: Polymer Systems For Nanofoamsmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept for these polymer blends nanofoams was similar: one phase acted as the matrix and the other dispersed phase served as a template for bubble nucleation and growth. For copolymers, nanofoams have been created mainly in PMMA‐based copolymers, such as poly(MMA‐co‐EMA) and poly(MMA‐co‐tBMA) . Polymer nanocomposites, which have some amount of nanoparticles dispersed in the polymer matrix, have been shown to generate nanofoams, such as in poly(MMA‐co‐EA) with silica nanoparticles and poly(MMA‐co‐EMA) with POSS .…”
Section: Introductionmentioning
confidence: 99%
“…12 Scanning electron microscope QUANTA 200 FEG of Thermo Fisher Scientific (USA). 13 At least 200 cells were analysed from multiple micrographs per foamed sample. 14 −− = (2) where g V is the geometric volume of the foam, p V is the pycnometer volume and s V is a penalty volume to account for the volume of the cells at the surface of the foam.…”
Section: Open Cell Contentmentioning
confidence: 99%